Performance of Concrete : Resistance of Concrete to Sulphate and Other Environmental Conditions; A Symposium in Honour of Thorbergur Thorvaldson - Swenson, Edwin George, 1911-; Thorvaldson, Thorbergur, 1883-1965 (Book collections on Project MUSE., 1968)
This book on concrete is a compilation of scientific and technical papers presented at a symposium held in honour of a Canadian scientist of international stature, the late Thorbergur Thorvaldson.